Using task analysis to promote engagement in special educational settings. Issue 2 (2nd July 2016) - Tan, Hong Chun; Hughes, Marilyn Roseanne; Toogood, Sandy
ABSTRACT: There is a clear expectation in European and UK policy guidelines that schools should support children with special educational needs to learn basic academic, social, and life-skills. This requires that children engage with activities across these three areas. While numerous studies have evaluated methods of increasing engagement in academic activities, few have focused on social and life-skills that promote independence. The purpose of the present studies was to evaluate the impact of task analysis on engagement in activities by pupils with intellectual disabilities. In the first study, a multiple-baseline design was used with three children to evaluate the effect of task analysis plus a system of red–amber–green recording on engagement levels. In the second study, a series of three single-case AB designs was used to compare engagement levels between activities with and without a task analysis plus prompts delivered from an iPad. The results showed that introducing task analyses increased engagement for the children who participated in both studies. Implications, limitations and areas for future research of both studies are discussed.